Integrated Application for Optimizing Budget Management and Procurement of Consumables in Laboratories in Educational Institutions Using Odoo - Vanya Syalmah; Umar Yunan Kurnia Septo Hediyanto; Taufiq Maulana Firdaus (Jurnal Indonesia Sosial Teknologi, 2024)
Laboratory management in Educational Institutions is important to support students' practical learning because laboratories are a means for students to delve into the material directly. An important aspect of laboratory management is budget management and consumables. Not a few Educational Institutions use spreadsheets to manage the budget and procurement of Consumables, which are often inefficient and poorly integrated. These limitations make it difficult to monitor budgets and the status of goods requests in real-time, hinder transparency, and increase the risk of human error, which can ultimately reduce accountability in laboratory management. This research aims to develop a more integrated budget management and procurement system for Consumables using Enterprise Resource Planning (ERP) with  Odoo software, involving the Accounting and Purchase modules. The QuickStart method is used to ensure smooth implementation by actively involving users throughout the development cycle. This system includes budget creation and monitoring, purchase order creation, and validation of goods received. The results of the Black Box Testing and Expert Judgement show that the developed system has met all the testing objectives, although improvements are still needed, such as the addition of graphs for budget visualization. The implementation of this system is expected to increase transparency and accountability in budget management and procurement of consumables in educational institutions.